Novel nanoparticles with Cr3+ substituted ferrite for self-regulating temperature hyperthermia. Issue 37 (20th July 2017) - Zhang, Wei; Zuo, Xudong; Niu, Ying; Wu, Chengwei; Wang, Shuping; Guan, Shui; Silva, S. Ravi P.
Abstract : Cr 3+ was substituted into Co–Zn ferrite to adjust the Curie temperature and coercivity for self-regulating hyperthermia temperature. Abstract : For hyperthermia to be used under clinical conditions for cancer therapeutics the temperature regulation needs to be precise and accurately controllable. In the case of the metal nanoparticles used for such activities, a high coercivity is a prerequisite in order to couple more energy in a single heating cycle for efficient and faster differential heating. The chemically stable Co–Zn ferrite nanoparticles have typically not been used in such self-regulating hyperthermia temperature applications to date due to their low Curie temperature usually accompanied by a poor coercivity. The latter physical property limitation under clinically applied magnetic field conditions (frequency: 100 kHz, intensity: 200 Oe) restricts the transfer of a reasonable heat energy, and thus limits the hyperthermia efficiency. Here, we report a novel Cr 3+ substituted Co–Zn ferrite (Zn0.54 Co0.46 Cr0.6 Fe1.4 O4 ), whose Curie temperature and coercivity values are 45.7 °C and 174 Oe, respectively. Under clinically acceptable magnetic field conditions, the temperature of these nanoparticle suspensions can be self-regulated to 44.0 °C and, most importantly with a specific absorption rate (SAR) of 774 W kg −1, which is two-fold higher than the SAR standard for magnetic nanoparticles used in hyperthermia (300 W kg −1 ). The evaluation of the in vitro cytotoxicity of the nanoparticles reports a low toxicity, which points to a novel set of magnetic nanoparticles for use in self-regulating hyperthermia.